The Influence of Occupational Safety and Health on Employee Work Productivity (Study on the Kisaran Majalengka Dam Project of Pt. Adhi Karya (Persero) Tbk) - Pipih Sopiyan; Haris Fauzi; Asep Qustolani; Windi Febriani (Fakultas Ekonomika dan Bisnis Universitas Majalengka, 2023)
Issues regarding occupational safety and health are important and often overlooked. This is evident from the significant occurrence of workplace accidents. Type, nature, condition and location of work in construction projects that tends to be dangerous resulting in a relatively high level of work accidents that occur to workers compared to other industries so it affects work productivity. The goal of this study is to determine the role that workplace health and safety plays in influencing worker output. The methodology employed for this study involves the utilization of a survey approach, employing both descriptive and verification methods. The population of this research consist of the workforce employed at PT. Adhi Karya (Persero) Tbk Majalengka Rentang Dam Project. This research employed a non-probability sampling strategy, specifically the saturation sampling method. The study's sample size was 60 participants. The data analysis makes use of numerous techniques, the t-test for hypothesis testing and other statistical methods such as the classical assumption test, multiple regression analysis, determination coefficient assessment, model feasibility study, and so on. The study method followed a survey format and combined descriptive and verification techniques. Employee productivity was found to be affected by both workplace safety and occupational health, as predicted by the study's hypotheses.